Monte Carlo thermodynamic and structural properties of the TIP4P water model: Dependence on the computational conditions - Cordeiro, JMM (Soc Brasileira Quimica, 1998)
Classical Monte Carlo simulations were carried out on the NPT ensemble at 25 degrees C and 1 atm, aiming to investigate the ability of the TIP4P water model [Jorgensen, Chandrasekhar, Madura, Impey and Klein; J. Chem. Phys., 79 (1983) 926] to reproduce the newest structural picture of liquid water. The results were compared with recent neutron diffraction data [Soper; Bruni and Ricci; J. Chem. Phys., 106 (1997) 247], The influence of the computational conditions on the thermodynamic and structural results obtained with this model was also analyzed. The findings were compared with the original ones from Jorgensen et al [above-cited reference plus Mel. Phys., 56 (1985) 1381]. It is notice that the thermodynamic results are dependent on the boundary conditions used, whereas the usual radial distribution functions g(O/O(r)) and g(O/H(r)) do not depend on them.
Keywords: Monte Carlo simulation; TIP4P water model; radial distribution function